The The Role of Parents And Teachers In Developing Early Childhood Social Emotions - Andyni Rizka Surya Amallya; Yes Matheos Lasarus Malaikosa; Jazilah Rohmatika (Journal of Art and Creativity in Early Childhood Education, 2025)
This study aims to describe the roles of parents and teachers and their strategies in developing the social-emotional skills of children aged 5-6 years, as well as the social-emotional development of children. The subjects of this study are parents and teachers, with the object of study being the social-emotional skills of children aged 5-6 years who have a certain level of development, the roles of parents and teachers, and the strategies implemented by teachers and schools. The research method used is a qualitative approach through case studies. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that children aged 5-6 years at TK Kemala Bhayangkari 1 Surabaya have relatively good development, as well as the role of parents and teachers in accompanying children in their growth and development process. The conclusion is that children demonstrate good results, marked by their ability to socialize and manage emotions positively. The collaboration between parents and teachers through effective communication also supports the optimization of children's social-emotional development in early childhood.